If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 450x = 650x + -1300 Reorder the terms: 450x = -1300 + 650x Solving 450x = -1300 + 650x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-650x' to each side of the equation. 450x + -650x = -1300 + 650x + -650x Combine like terms: 450x + -650x = -200x -200x = -1300 + 650x + -650x Combine like terms: 650x + -650x = 0 -200x = -1300 + 0 -200x = -1300 Divide each side by '-200'. x = 6.5 Simplifying x = 6.5
| -182=8(3p-1)-6 | | 4[m-6]=7m | | 50/7= | | -5+5[n+5]=-5n-30 | | sinx=0.81649 | | 26+4j=86 | | 7-2r=2r+3 | | 3(3y+3)+6=81 | | -4(19n+7)+11=-17-2n | | -9x-9t=-30 | | 3(5r-4)-4(r+9)= | | 1+3p=-17 | | x^2+y^2=2ax | | -30b=-27n-63 | | -7(5-8n)=-259 | | 176=-8(4n+2) | | 8r+3(r+8)=15+8r | | X=2(14.2)(1)/100 | | 24+6y=12x | | 32.5+2(11)(7)+(11)(5)= | | -7/-11=k/11 | | 14+8n+2n=7n+2 | | 10m-2=12m+3 | | 9x+8y+9z-(3x-4z)= | | 20x-60=285 | | 8x^2-30x-18=0 | | 248=-8(-4x-7) | | 10v+5=5(1+2v) | | log(7-6x)=0 | | 91=2x^2+3x+2 | | p2•p1/t1 | | 2(x-6)=35 |